Molten-Salt-Based Thermal Storage for Thermal Power Unit Plant Peaking - Fengying Ren; Fanxing Meng; Hao Liu; Haiyan Yu; Li Xu; Xiaohan Ren (Energies)
As the integration of renewable energy sources continues to increase, thermal power units are increasingly required to enhance their operational flexibility to accommodate grid fluctuations. However, frequent load variations in conventional thermal power plants result in decreased efficiency, accelerated equipment wear, and high operational costs. In this context, molten-salt thermal energy storage (TES) has emerged as a promising solution due to its high specific heat capacity and thermal stability. By enabling the storage of surplus energy and its regulated release during peak demand periods, molten salt TES contributes to improved grid stability, reduced start-up frequency, and minimized operational disturbances. This study employs comprehensive thermodynamic simulations to investigate three representative schemes for heat storage and release. The results indicate that the dual steam extraction configuration (Scheme 3) offers the highest thermal storage capacity and peak-load regulation potential, albeit at the cost of increased heat consumption. Conversely, the single steam extraction configurations (Scheme 1 and 2) demonstrate improved thermal efficiency and reduced system complexity. Furthermore, Scheme 3, which involves extracting feedwater from the condenser outlet, provides enhanced operational flexibility but necessitates a higher initial investment. These findings offer critical insights into the optimal integration of molten-salt thermal-storage systems with conventional thermal power units. The outcomes not only highlight the trade-offs among different design strategies but also support the broader objective of enhancing the efficiency and adaptability of thermal power generation in a renewable-dominated energy landscape.